2014
DOI: 10.1001/jamapediatrics.2013.5296
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Children’s Exposure to Violence, 2003 to 2011

Abstract: Victimization surveys with general population samples confirm patterns seen in police data and adult surveys. Crime and violence have been declining in the child and youth population as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 25 publications
(33 reference statements)
2
37
0
10
Order By: Relevance
“…Perhaps as a result, there are signs that some indicators of school victimization and other violence may be decreasing in the general population of school-age youth. Results from the National Youth Risk Behavior Survey found that weapon-carrying and fighting at school declined from 1991 to 2003and from 1999(Centers for Disease Control, 2005. Perlus and colleagues, analyzing waves of a national survey of 6 th through 10 th grade students, found that physical fighting and in-school bullying victimization both declined significantly from 1998 to 2010, though when genders were analyzed separately, results for being bullied were significant only for boys (Perlus, BrooksRussell, Wang & Iannotti, 2014).…”
Section: Two Decades Of Changementioning
confidence: 99%
“…Perhaps as a result, there are signs that some indicators of school victimization and other violence may be decreasing in the general population of school-age youth. Results from the National Youth Risk Behavior Survey found that weapon-carrying and fighting at school declined from 1991 to 2003and from 1999(Centers for Disease Control, 2005. Perlus and colleagues, analyzing waves of a national survey of 6 th through 10 th grade students, found that physical fighting and in-school bullying victimization both declined significantly from 1998 to 2010, though when genders were analyzed separately, results for being bullied were significant only for boys (Perlus, BrooksRussell, Wang & Iannotti, 2014).…”
Section: Two Decades Of Changementioning
confidence: 99%
“…Although overall child maltreatment rates fell by 26 percent over the nine-year period, this was largely driven by a significant decline in emotional abuse, with physical abuse rates remaining unchanged. Child witnessing or indirect victimization decreased by 28 percent from 2003 to 2011 (Finkelhor, Shattuck, et al, 2014). The decline in most forms of childhood victimization mirrored a decline in violent crime victimization nationally.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Although rates of children's exposure to violence have been declining, in 2011, 58 percent of children in a nationally representative sample had been exposed to violence in the past year, with 48 percent exposed to multiple types of violence (Finkelhor, Shattuck, et al, 2014;Finkelhor, Turner, et al, 2015). The immediate negative consequences of children's exposure to violence include depression, anxiety, behavior problems, and trauma symptoms, and many of these issues persist into adulthood.…”
Section: Summary Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, studies using nationally representative data have shown that black and Latino children (who are more likely to live in urban contexts) are twice as likely as white children to be assaulted with a weapon, to be assaulted by multiple assailants, and to be injured during assault. Furthermore, black children are three times more likely to be exposed to shootings and twenty times more likely to witness a murder than white children (Finkelhor et al 2005; see also Finkelhor et al 2011Finkelhor et al , 2014. Using Add Health data, Harding (2010:29) reports that children in communities where poverty rates exceed 40 percent are more than three times as likely to feel unsafe as those in nonpoor neighborhoods.…”
mentioning
confidence: 99%